Genetically Regulated Bilirubin and Risk of Non-alcoholic Fatty Liver Disease: A Mendelian Randomization Study - Luo, Lei; An, Ping; Jia, Xinyong; Yue, Xiaobian; Zheng, Sujun; Liu, Shuang; Chen, Yu; An, Wei; Winkler, Cheryl A.; Duan, Zhongping (Frontiers in Genetics, 2018)
Mildly elevated serum bilirubin levels were reported to be associated with decreased risk of nonalcoholic fatty liver disease (NAFLD). Whether this is a causal relationship remains unclear. We tested the hypothesis that genetically elevated plasma bilirubin levels are causally related to reduce risk of NAFLD. A total of 403 eligible participants were enrolled. NAFLD was determined by liver ultrasonography. The uridine diphosphate glucuronosyltransferase 1A1 (UGT1A1) gene variants (UGT1A1*6 and UGT1A1*28) were genotyped through sequencing. We applied a Mendelian randomization approach to assess the effects of genetically elevated bilirubin levels on NAFLD. NAFLD was diagnosed in 19% of participants in our study (NAFLD=76; Non-NAFLD=327). The variants of UGT1A1*28 and UGT1A1*6 were strongly associated with increased total bilirubin (TB), direct bilirubin (DB) and indirect bilirubin (IB) levels (each P < 0.001). These two common variants explain 12.7% (TB), 11.4% (IB), and 10.2% (DB) of the variance in bilirubin levels, respectively. In logistic regression model, after multifactorial adjustment for sex, age, aminotransferase (ALT), white blood count (WBC) and body mass index (BMI), variant UGT1A1*28 (OR=1.39; 95%CI: 0.614-3.170; P = 0.43) and UGT1A1*6 (OR=1.64, 95%CI, 0.78-3.44; P = 0.19) genotypes were not significantly associated with the risk of NAFLD. Moreover, the plasma bilirubin level (TB, IB and DB) were not significantly associated with the risk of NAFLD (P > 0.30). A Mendelian randomization analysis of the UGT1A1 variants suggests that bilirubin is unlikely causally related with the risk of NAFLD.